2021
DOI: 10.28991/scimedj-2021-0303-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rewards on Work Commitment of Nurses at Surgical and Medical Section (SMS) of National Hospital

Abstract: Background: Nurses are an essential component of health workforce. Therefore rewarding nurses is important to provide better service to the clients. The main purpose was to describe the effect of rewards on the work commitment of nurses at the SMS of National hospital. Objectives: to identify intrinsic and extrinsic rewards cause to the level of work commitment of nurses at SMS of National hospital, to determine the level of work commitment of nurses at SMS of National hospital, to measure the effect of socio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…This improvement might be related to several reasons, such as providing the nurse with booklet, using of audiovisual aids, frequent demonstration, providing better facilities and supplies that facilitate learning and better communication adequate number of nurses in ICU. Also, this result was supported by Senanayake et al (2021) (43) . who revealed that continuing professional development programs, which aim to enhance health professionals practice and improve patients out comes .…”
Section: Demographic Characteristics Of the Studied Nursessupporting
confidence: 69%
“…This improvement might be related to several reasons, such as providing the nurse with booklet, using of audiovisual aids, frequent demonstration, providing better facilities and supplies that facilitate learning and better communication adequate number of nurses in ICU. Also, this result was supported by Senanayake et al (2021) (43) . who revealed that continuing professional development programs, which aim to enhance health professionals practice and improve patients out comes .…”
Section: Demographic Characteristics Of the Studied Nursessupporting
confidence: 69%
“…Moreover, the participants of this study repeatedly mentioned the understanding, importance and impact of internal rewards, such as personal satisfaction from completing an activity and gaining a sense of competence. Other studies have acknowledged the importance of intrinsic rewards in increasing motivation and improving job performance (Anjum, Islam, Choudhury, & Saha, 2021;Manzoor, Wei, & Asif, 2021;Senanayake, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Especially the Sri Lankan service sector healthcare industry nowadays struggles with a high employee turnover. Nursing staff leave work without prior notice, and migration becomes a critical trend (Senanayake, 2021). Scholars have pointed out that the country encounters considerable nursing workforce scarcity (SANC, 2006, as cited in Hellerawa & Adambarage, 2015.…”
Section: Problem Statementmentioning
confidence: 99%